Interpretational Variations of Nepali Poems Translated to English - Bhusal, Tilak; Baudel , Pujan (International Journal of Language and Literary Studies, 2025)
Teaching of poetry has contributed much to the field of English language teaching; however, studies on how interpretational variations through translation are scarce. This study explores the interpretational variations that emerge when teaching poetry in the classroom. The research examines a selection of Nepali poems and their English translations to identify the shifts in meaning, tone, cultural context, and stylistic elements that occur during the translation process. Additionally, it highlights the inherent challenges in translating poetic works by employing a comparative analysis, such as preserving the original emotional depth, cultural nuances, and linguistic intricacies. The research underscores the importance of a nuanced approach to translation that balances fidelity to the original text with the creative adaptation necessary to convey the essence of poetry in a different language. For this research, five major poems in Nepali were selected which were translated into English: Pinjadako Suga (Parrot in the Cage) by Lekhanath Poudel, Aaimai (Woman) by Banira Giri, Ghantaghar (The Clock Tower) by Bhu Pi Serchan, Naya Barsa (New Year) by Parijat and The Brook by Laxmi Prasad Devkota. The study is also based on the subjective interpretation made by the teachers, which creates variation in meaning. The findings reveal that while translations strive to remain faithful to the source texts, significant variations often arise due to differences in linguistic structures, cultural references, and the translators' subjective interpretations. These variations can lead to a reimagining of the poems, offering new dimensions and perspectives to the readers of the translated versions. The study is expected to contribute to the broader discourse on translation studies, highlighting the complex interplay between language, culture, and the interpretation of poems.